2022
DOI: 10.1001/jamanetworkopen.2022.25810
|View full text |Cite
|
Sign up to set email alerts
|

Association of Administration of Surfactant Using Less Invasive Methods With Outcomes in Extremely Preterm Infants Less Than 27 Weeks of Gestation

Abstract: IMPORTANCEThe inclusion of less invasive surfactant administration (LISA) in the care of preterm infants has been found to be beneficial for respiratory outcomes. Recently, the OPTIMIST trial found higher mortality rates in the subgroup of infants born at 25 to 26 weeks' gestational age (GA) who received surfactant treatment while spontaneously breathing. OBJECTIVETo analyze outcomes among LISA-exposed, highly vulnerable babies born at less than 27 weeks' GA within the large-scale observational cohort of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Although these differences did not reach statistical significance, they demand caution. Of note, in contrast, the recently published investigation of the GNN in 6542 preterm infants born at 22 0/6–26 6/7 weeks’ GA documented lower risks of all-cause death and BPD or death in LISA-treated infants in experienced centres 46. However, a previous GNN study found increased rates of focal intestinal perforation (FIP) in the LISA group, primarily in the most immature babies born at 22–24 weeks 41.…”
Section: The Promise Of Non-invasive Support: a Signal Blunted By Def...mentioning
confidence: 91%
See 4 more Smart Citations
“…Although these differences did not reach statistical significance, they demand caution. Of note, in contrast, the recently published investigation of the GNN in 6542 preterm infants born at 22 0/6–26 6/7 weeks’ GA documented lower risks of all-cause death and BPD or death in LISA-treated infants in experienced centres 46. However, a previous GNN study found increased rates of focal intestinal perforation (FIP) in the LISA group, primarily in the most immature babies born at 22–24 weeks 41.…”
Section: The Promise Of Non-invasive Support: a Signal Blunted By Def...mentioning
confidence: 91%
“…It is also reasonable to consider that targeting this intervention to those with surfactant deficiency would maximise the treatment effect and minimise exposure to the known short-term risks associated with the procedure, including laryngoscopy, bradycardia and hypoxaemia. The strategy of CPAP-assisted spontaneous breathing and early surfactant therapy via LISA—often within the first hour of life—is widespread in GNN centres and includes the tiniest babies 37 45 46. In ~60% of infants, this early treatment remains the only surfactant dose.…”
Section: The Promise Of Non-invasive Support: a Signal Blunted By Def...mentioning
confidence: 99%
See 3 more Smart Citations